Viewpoint: How to Teach Global Challenges? A Solution-Focused Approach - Thomas Hoffman (Environmental Association of Southern Africa, 2021)
Our present and our future are determined by massive global challenges. While the United Nations' Agenda 2030 attempts a global answer to cope with these challenges, schooling in general and Geography teaching in particular, have to find answers for how to deal with challenges such as climate change, loss of biodiversity, water scarcity, poverty or migration. Historically, a mainly problem-oriented teaching approach shaped the learning settings on these topics, with most of the lesson time dedicated to the problem. A solution-focused teaching approach, presented here, makes the solution the main focus in terms of time, thoughts, creativity and discussion, without neglecting the challenges. This approach considers principles of Education for Sustainable Development and contributes extensively to the key competences it strives for. By means of concrete examples from Germany and India and suitable elements such as 'stories of change', this paper explains and reflects on this innovative teaching approach.